Image of reality and reality of image: the problem of civilizational identity in the light of the experience of socio-cultural “Frontier”: Образ реальности и реальность образа: проблема цивилизационной идентичности в свете опыта социокультурного «пограничья» - Shemyakin, Iakov (Przegląd Wschodnioeuropejski, 2020)
The article deals with the problem of civilizational identity in the light of the experience of socio-cultural “borderland”. The author defines identity as a state of community or personality that has acquired the meaning of existence and, thus, integrity. Under the condition of identity differ in the image of identity and the identificational pivot-invariant. The image of identity is a spiritual reality, the basis of the “spiritual body” of civilization, reflecting its ideas about itself, its place in history. Identifying a core-invariant is the reality of the connection of the spiritual and the material “body” of civilization. In its spiritual aspect it is either the same as (fully or partially) with the image of civilization, or is in conflict (to varying degrees). The key characteristic of civilizations of the “borderline” type-the dominant of diversitydetermined the specificity of their identification sphere: relatively frequent (in comparison with the great “classical” civilizations of the East and the West) change of identity images while maintaining the same identification invariant – the process of interaction of diverse traditions. According to the author, the experience of civilizational “borderland” is especially valuable in modern conditions. The main conclusions that can be drawn from the study of this experience. First, it is possible to achieve the unity of the civilizational system in the conditions of the dominant diversity. Secondly, it is possible to preserve the identificational core-invariant with a relatively frequent (again, in comparison with the great “classical” civilizations of the East and the West) change in the images of the identity of civilizations of the “border” type.